Vulnerability of mesostriatal dopaminergic neurons in Parkinson's disease - Tomás González-Hernández; Tomás González-Hernández; Ignacio Cruz-Muros; Ignacio Cruz-Muros; Domingo Afonso-Oramas; Josmar Salas-Hernández; Javier CastroHernández (Frontiers Media S.A., 2010)
The term vulnerability was first associated with the midbrain dopaminergic neurons eighty-five years ago, before they were identified as monoaminergic neurons, when Foix and Nicolesco (1925) reported the loss of neuromelanin containing neurons in the midbrain of patients with post-encephalitic Parkinson's disease (PD). A few years later, Hassler (1938) showed that degeneration is more intense in the ventral tier of the substantia nigra compacta than in its dorsal tier and the ventral tegmental area, outlining the concept of differential vulnerability of midbrain dopaminergic (DA-) neurons. Nowadays, we know that other neuronal groups degenerate in PD, but the massive loss of nigral DA-cells is its pathological hallmark, having a pivotal position in the pathophysiology of the disease as it is responsible for the motor symptoms. Data from humans as well as cellular and animal models indicate that DA-cell degeneration is a complex process, probably precipitated by the convergence of different risk factors, mediated by oxidative stress, and involving pathogenic factors arising within the DA-neuron (intrinsic factors), and from its environment and distant interconnected brain regions (extrinsic factors). In light of current data, intrinsic factors seem to be preferentially involved in the first steps of the degenerative process, and extrinsic factors in its progression. A controversial issue is the relative weight of the impairment of common cell functions, such as energy metabolism and proteostasis, and specific dopaminergic functions, such as pacemaking activity and DA handling, in the pathogenesis of DA-cell degeneration. Here we will review the current knowledge about the relevance of these factors at the beginning and during the progression of PD, and in the differential vulnerability of midbrain DA-cells.